Depression screening and advisory service provided by community pharmacist for depressive students in university - Wiraphol Phimarn (2018)
© 2015, Phimarn et al. Background: Depressive symptom among adolescent is prevalent but advisory service for this symptom is limited, particularly in university. Objectives: (1) To identify depressive students in health science faculties, (2) To evaluate the consequence of depression advisory service by community pharmacist, compared between a group counseling and an individual one. Methods: A two-phase study was designed—a cross-sectional study followed by an experimental study. Health science students were screened by CES-D questionnaire. The prevalence and predictors of depressed mood were determined. Depressive students were then invited to the experimental study. Participants were assigned into 2 groups, by stratified random sampling, and followed up for 16 weeks. Group 1 received a group counselling, group 2 received an individual counselling from a trained pharmacist. Outcomes measured were the CES-D score and quality of life. Results: The prevalence of depressed mood students was 13.7 % (195/1421). Students in year 2nd and year 3rd, nursing and medicine students, and GPA were strongly associated with the CES-D score (P < 0.05). Sixty-eight depressive students were assigned into the experiment. The CES-D scores of both groups were significantly reduced from the baseline (P < 0.001). The post-test score of group 2 was lower than group 1 (17.7 ± 4.5 vs 20.1 ± 4.6, P = 0.038). At week 16, both counselling types significantly increased mean score of physical health (P < 0.001) whereas score of mental health was increased significantly only by the individual counselling, from 37.9 ± 9.9 to 43.1 ± 8.4 (P = 0.036). Conclusions: Depressive symptom among health science students is considerably high. Year of study, faculty and GPA are significant predictors of this disorder. Trained community pharmacists can effectively screen and provide advisory service. Individual counseling is more effective than using group advice.